Foot and Ankle Offset (FAO) Does Not Reflect the Actual Hindfoot Alignment in Cases Involving Ankle and/or Sagittal Foot and Ankle Deformities. Issue 4 (November 2022) - Li, Shuyuan; Sempson, Sera; Gu, Wanjun; Wang, Chao; Zhu, Mingjie; Zhang, Ming-Zhu; Hunt, Kenneth J.; Myerson, Mark S.
Category: Hindfoot; Ankle; Midfoot/Forefoot Introduction/Purpose: The foot and ankle offset (FAO) was developed as a 3D biometric tool to measure hindfoot alignment on weightbearing CT (WBCT) scans. It corresponds to the offset between the hindfoot-to-forefoot midline and the talus and is reported as a percentage of foot-length. (1) Recently, with increased availability of WBCT in both research and clinical practice, the FAO has been widely used for hindfoot alignment assessment. (2) However, after extensive review of WBCT scans the authors of this study have noticed that FAO has a high false negative rate. This study aimed to demonstrate why FAO is inadequate in assessing 3D hindfoot alignment using both case examples and mathematical algorithms. Methods: This was a retrospective study including a cohort of 31 cases with various clinical diagnoses selected from a data base of WBCT in 260 patients. The deformities included valgus or varus ankle deformities, hindfoot deformities combined with sagittal plane deformities of the foot and ankle, rocker bottom foot deformity, ankle equinus, metatarsus primus elevatus, and first metatarsal plantarflexion. All of the latter deformities caused one or more parts of the triangular base for FAO evaluation (the 1st metatarsal, the 5th metatarsal and the calcaneus) to remain off the floor. The medical charts and WBCT scans of each patient were reviewed to evaluate the deformities in more detail. The FAO was measured by two fellowship trained foot and ankle surgeons separately. The clinical and radiographic diagnoses were compared with the FAO value to determine the accuracy and utility of the latter measurement. Limitations of FAO as a semi 3D tool using the tripod theory in assessing the hindfoot alignment were also demonstrated mathematically. Results: For each of these 31 cases examined, the hindfoot alignment information reflected by the FAO value was vastly different from the clinical and imaging study findings. (Table 1). Using the reference value for FAO (Normal 2.3% ± 2.9%, Varus −11.6%± 6.9%, and Valgus 11.4% ± 5.7%), 24 out of 31 cases in the cohort had a normal FAO value, however, among them there were 7 with a valgus ankle or distal tibia plus a normal or cavovarus hindfoot, 2 varus ankles with a normal hindfoot, 1 varus ankle with a valgus hindfoot, 3 cavovarus feet, 1 clubfoot, 1 equinus ankle with cavovarus foot, 2 equinus ankle with severe valgus hindfoot, 4 severe valgus hindfoot and 1 varus hindfoot with sagittal plane deformities, 2 Muller Weiss Disease; 5 out of 31 cases had a varus FAO value, but they all had a valgus ankle with either a varus hindfoot or sagittal plane deformities; 2 out of 31 cases had a valgus FAO value, however both cases had a valgus ankle with a varus hindfoot. Thorough algorithm and geometric evidence were provided. Conclusion: FAO has a very limited capacity to reflect hindfoot deformities, understandable when analyzing how the FAO is designed and measured mathematically. It is not a 3D tool. It does not include the level of the ankle nor the tibia, therefore it is not appropriate nor capable to be used as a hindfoot alignment evaluation tool. The tripod and talus projection theories cannot reflect sagittal plane deformities or coronal plane rotation, and false results are inevitably generated. Reference: 1. Lintz F, Barton T, Millet M, Harries WJ, Hepple S, Winson IG. Ground reaction force calcaneal offset: a new measurement of hindfoot alignment. Foot Ankle Surg. 2012;18(1):9-14. 2. de Cesar Netto C, Day J, Godoy-Santos AL, Roney A, Barbachan Mansur NS, Lintz F, Ellis SJ, Demetracopoulos CA. The use of three-dimensional biometric Foot and Ankle Offset to predict additional realignment procedures in total ankle replacement. Foot Ankle Surg. 2022 Feb 16:S1268-7731(22)00036-4.